Analisis Teoritis Tentang Fungsi Humas dalam Konteks Pendidikan Dasar - Rifqa Anisa Syifa; Aprilia Amelia; Artieka Devi Oktaviana; Dwi Khusnul Ramadhani; Muhammad Hanif Akmaluddin; M. Jiyad Khairani; Suhaimi Suhaimi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The role of public relations in basic education institutions is not just about sharing information, but also about building constructive relationship between the school and its surrounding social environment. This article aims to examine the theoretical role of public relations in the context of primary education by placing it within the framework of organizational communication and educational management. The writing was done through literature review by analyzing various relevant sources to understand the concepts, roles, and importance of public relations in the basic education system. The study shows that communication plays a strategic role in building two-way conversational communication, increasing parent and community involvement, and supporting transparency in the management of the institution. In addition, the public relations team helps shape public perception and maintain the educational institution’s reputation by managing accurate and ethical Information. In theory the effectiveness of the public relations function depends managerial ability, open communication, and how well the school’s policies match the needs of stakeholders. Therefore, strengthening the role of public relations is an essential part of efforts to achieve a responsive and public trust-oriented basic education governance system.